Correlates of Adherence of Multimodal Non-pharmacological Interventions in Older Adults With Mild Cognitive Impairment: A Cross-Sectional Study - Sun, Xue; Wang, Lina; Shen, Xinhua; Huang, Cheng; Wei, Zhuqin; Su, Liming; Wang, Simeng; Liu, Xiaoshen; Zhen, Xueting (Frontiers in Psychiatry, 2022)
Background: Non-pharmacological interventions are promising for delaying cognitive decline among older adults with mild cognitive impairment (MCI). Although some studies have demonstrated the adherence rate and factors influencing the participation in the single modality non-pharmacological intervention, little is known about the level and correlates of adherence to multimodal non-pharmacological interventions (MNPIs) among older adults with MCI. Objective: This study aimed to explore adherence characteristics and the correlates of adherence to MNPIs among older adults with MCI. Methods: A cross-sectional design was employed. Community-dwelling older adults aged 60 years and over were recruited from senior community centers and healthcare centers in Huzhou from March 2019 to December 2020. Data were collected by a general information questionnaire and an adherence scale of cognitive dysfunction management (AS-CDM) for older adults with MCI. Hierarchical regression analyses were applied to explore the correlates of adherence to MNPIs. Results: A total of 216 completed questionnaires were finally analyzed. Of these, 68.52% were female, and 45.4% of the participants had no less than 6 years of education. The overall mean score for adherence was 117.58 (SD=10.51) out of 160, equivalent to 73.49 in the hundred-mark system, indicating a medium-level adherence to MNPIs for older adults with MCI. Of the five dimensions of adherence (AS-CDM), self-efficacy yielded the highest score, and the lowest was perceived barriers. The univariate analysis showed that the factors associated with the adherence to MNPIs were: regular physical exercise, meat-vegetable balance, absence of multimorbidity, high level of education, living alone, and living in urban (p<0.05). In the hierarchical regression analysis, the final model explained 18.8% of variance in overall adherence (p<0.01), which high school (Beta=0.161, p<0.05), college and above more (Beta=0.171, p<0.05), meat-vegetarian balance (Beta=0.228, p<0.05), regular physical exercise (Beta=0.234, p<0.05), and presence of multimorbidity (Beta=-0.128, p<0.05) significantly contributed to adherence. In addition, nearly 80% of older adults with MCI preferred MNPIs. Conclusion: Early assessment and management of adherence to MNPIs were essential among older adults with MCI. Furthermore, the findings elucidate several critical areas to target in interventions to improve adherence to MNPIs in older adults with MCI. Clinical Trial Registration: ChiCTR1900020950. http://www.chictr.org.cn/showproj.aspx?proj=35363.